Stabilizability of nonlinear infinite dimensional switched systems by measures of noncompactness in the space c0. (August 2017) - Zawiski, Radosław
Abstract: This article studies the problem of stabilizability of nonlinear infinite dimensional switched systems. The switching rule is arbitrary and takes place between a countably infinite number of subsystems, each of which is represented by a differential equation in some Banach space. Using a topological notion of a (locally finite) cover and the Hausdorff measure of noncompactness in the c 0 space, we show how the problem of approximate stabilizability of switched systems can be cast into a sequential framework and dealt with. Examples of application are given.